Influence of potassium on the productivity and quality of potato: A Review - Amanpreet Singh; Harmandeep Singh Chahal; Gurbax Singh Chinna; Ranvir singh (Environment Conservation Journal, 2020)
Potato ranks one of the most important food crops after rice, wheat, and other field crops. A healthy potato crop removes about 1.7 to 2.3 quintals of potassium ha-1, illustrating that the potassium requirement for potatoes is much higher than that of grains. Being a shallow root crop, the effectiveness of using potassium fertilizers on potatoes varies from 50 to 60 percent. Potassium nutrition plays an important role in increasing the potato yield, either due to the formation of large tubers or the increase in the number of tubers per plant. Among the integrated nutrient management in potatoes, farmyard manure improves the absorption and availability of potassium for potato plants. Potassium protects against frost and drought stress in plants and reduces the incidence of diseases or pests. Potassium availability also decreases the concentration of reducing sugar and improves the colour and quality of potato chips. Potassium sulfate improves potato quality better than sources of potassium chloride.